ИСПОЛЬЗОВАНИЕ РЕШЕНИЙ ОБРАТНОЙ ЗАДАЧИ ЛИНЕЙНЫХ ПРОЦЕССОВ АВТОРЕГРЕССИИ ДЛЯ МОДЕЛИРОВАНИЯ ВИБРАЦИОННЫХ СИГНАЛОВ УЗЛОВ ЭЛЕКТРОТЕХНИЧЕСКОГО ОБОРУДОВАНИЯ - Зварич, В.Н. (Інститут електродинаміки НАН України, Київ, 2016)
A method for finding the characteristic function of the generating process for a linear autoregressive process with a negative binomial distribution is considered. To solve such a problem, which is called the inverse problem, the properties of the characteristic function of a stationary linear random process of autoregression are used, which can be represented both in the Kolmogorov canonical form and in the form of a linear random process with discrete time, as well as the transformation kernel for such a process. An example of finding a characteristic function for a second-order linear autoregressive process with a negative binomial distribution is presented. The application of the obtained results to find the characteristic function of the vibration signal of a wind generator is shown. References 14, figure 1.